Woodland Expansion in Upland National Parks: An Analysis of Stakeholder Views and Understanding in the Dartmoor National Park, UK - Olivia FitzGerald; Catherine Matilda Collins; Clive Potter (Land, 2021)
Woodland expansion on a significant scale is widely seen to be critical if governments are to achieve their net zero greenhouse gas ambitions. The United Kingdom government is committed to expanding tree cover from 13% to at least 17% in order to achieve net zero by 2050. With much lowland area under agricultural production, woodland expansion may be directed to upland areas, many of which are national parks under some degree of conservation jurisdiction. This may prove to be controversial, requiring full engagement with the interests of those individuals with a stake in their protection and management. In this paper, we explore how a range of stakeholders view the prospect of woodland expansion in Dartmoor National Park in southwest England, UK. Fifteen stakeholders—a mix of key informants and farmers—were shown different woodland expansion scenarios in map form and consulted using semi-structured interviews. The findings suggest widespread enthusiasm for woodland expansion, but with significant differences in terms of the scale and approach. Stakeholders raised topics of biodiversity gain, climate change mitigation, environmental benefits, cultural ecosystem gain, and forest crop benefits. Caution was expressed regarding target setting, the place of woodland expansion in the national debate, and the potential for harm from inappropriate new planting. The constraints identified were land tenure patterns, notably tenancy insecurity and ‘common land’ challenges, historical farming policy and culture, landscape objectives, and future policy design.